Ecological Risk Assessment, Interpolation, and Pollution Source Identification of Toxic Elements in Soils and Leaves of the Vineyard of Malayer County - Mohamad Parsi Mehr; Samar Mortazavi (Hamadan University of Medical Sciences, 2019)
Grape is a strategic product in the county of Malayer. Despite the great importance and existence of polluted resources in the vicinity of vineyards in Malayer, there are few studies conducted in this regard. To evaluate the pollution level of toxic elements in these vineyards, 20 sampling stations were selected randomly and samples of garden soil and leaves of grapevine species were collected. After the acidic digestion of the samples, the concentrations of the heavy metals were measured using atomic absorption spectrometer. Then, the indices of contamination factor (Cf), geo-accumulation index (Igeo), biological accumulation coefficient (BAC), and ecological risk index (RI) were calculated. According to the results obtained for Igeo and Cf indices, the soil in the study region was moderately contaminated with copper. However, the ecological risk index and BAC of the studied region were low. To investigate the spatial distribution of copper in the studied region, the spatial distribution map was prepared. To locate the source of copper contamination and investigate the effect of various land uses on the amount of contamination, land use map (LUM) of vineyards was generated. To this end, images were downloaded from Landsat Satellite, and after the exertion of various corrections on the images based on the supervised classification method, the LUM with agricultural, residential, vineyard, brick furnace and pasture classes was prepared. The comparison of the LUM and the copper contamination map illustrated that the copper contamination was higher in the places with urban and adobe furnace land-use types.